2023
DOI: 10.4062/biomolther.2023.035
|View full text |Cite
|
Sign up to set email alerts
|

Meclofenamate Suppresses MUC5AC Mucin Gene Expression by Regulating the NF-kB Signaling Pathway in Human Pulmonary Mucoepidermoid NCI-H292 Cells

Abstract: The current study aimed to reveal the potential effect of meclofenamate, a nonsteroidal anti-inflammatory drug, on the gene expression of airway MUC5AC mucin. Human pulmonary mucoepidermoid NCI-H292 cells were pretreated with meclofenamate for 30 min and stimulated with phorbol 12-myristate 13-acetate (PMA) for 24 h. Thereafter, the effect of meclofenamate on the PMAinduced nuclear factor kappa B (NF-kB) signaling pathway was assessed. Meclofenamate inhibited glycoprotein production and mRNA expression of MUC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Additionally, the cells are widely employed in studies related to bronchial-associated disorders and inflammatory responses. This cell line serves as a valuable model for pulmonary diseases, particularly those associated with mucin production activity [ 32 , 33 ]. In our previously published paper, we have already demonstrated that the levels of MUC5AC, a major component of mucin, are significantly increased when NCI–H292 cells are treated with PMA, EGF, TNF, cigarette smoke extract, or acrolein [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cells are widely employed in studies related to bronchial-associated disorders and inflammatory responses. This cell line serves as a valuable model for pulmonary diseases, particularly those associated with mucin production activity [ 32 , 33 ]. In our previously published paper, we have already demonstrated that the levels of MUC5AC, a major component of mucin, are significantly increased when NCI–H292 cells are treated with PMA, EGF, TNF, cigarette smoke extract, or acrolein [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4, 5) TNF‐α induces the secretion of MUC5AC and MUC5B by activating two signaling pathways: PLC→DAG→PKC→NO→cGMP→PKG, 54 ERK1/2→p38MAP→MSK1→cAMP 39 . (6) TNF‐α can promote the expression of MUC5AC gene by inducing nuclear translocation of NF‐κB p65 subunit 37 . (7) TNF‐α can impaired GR‐α nuclear translocation and inhibit the expression of NF‐κB p65, thus inhibiting the expression of MUC1 gene 51 .…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
“…For example, Lee et al 36 . found that TNF‐α could induce expression of the MUC5AC gene via nuclear translocation of the p65 subunit in NF‐κB induced by TNF‐α in human respiratory epithelial cells, and that p65 was a transcription factor that regulated MUC5AC gene expression 37 . Song et al 38 .…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
See 2 more Smart Citations